Comprensión lectora y rendimiento académico en estudiantes de quinto de secundaria de una institución educativa del Callao - Hernández Romero, Ysabel Rosario (2010)
This research is related to the descriptive correlational study. It has as objective to establish the relation that exists between reading comprehension and academic achievement. The evaluation was taken to 5th grade students that are about to finish high school. For it there was selected a sample formed by 94 students, of both sexes from a public school located in Callao. For testing the reading comprehension, it was used the Tapia’s reading comprehension test -1982, which is a tool with a collective use. First of all, was considered the last year students’ averages in the subjects of Language, History, Geography, Economy and science in order to get the academic efficiency. For the statistical analysis, was developed the Pearson’s co relation. So, the results showed the positive and meaningful co relation between the reading comprehension and the academic achievement, just as in the subjects in evaluation. To conclude, we believe in this cause-effect, a student that reads more and understand what the text means, has good grades and academic achievement.